Gait in children and adolescents with idiopathic musculoskeletal pain - Maria da Conceição Costa (Advances in Rheumatology, 2019)
Abstract Introduction Musculoskeletal pain is a constant complaint in pediatric practice. The pain may be related to a number of organic diseases and / or be part of the amplified musculoskeletal pain syndromes. Idiopathic musculoskeletal pain (IMSP) is defined as the presence of intermittent pain in three or more body regions for at least three months, excluding organic diseases that could explain the symptoms. Objective To study the gait of children and adolescents with IMSP by dynamic baropodometry. Methodology Thirty-two patients with IMSP and 32 healthy controls, matched by age, sex, social class, and body mass index (BMI) were enrolled. All were evaluated for pain intensity through the visual analogue scale (VAS) and gait evaluation using dynamic baropodometry. Results The mean age of the IMSP group was 13.6 years (SD = 2.1, range 9.8–16.9) and of the control group was 13.5 years (SD = 2.0, range 9.6–16.5). The mean pain scale was 5.4 cm in the IMSP group and 0 cm in the control group (p < 0.001). In gait, the mean right foot velocity of the IMSP group was significantly lower (p = 0.034), the time of the step of the IMSP group was significantly higher (p = 0.003) and the pace of the IMSP group was significantly lower (p = 0.001). Conclusion In our study we observed differences between the gait of children with IMSP and healthy controls according to the dynamic baropodometry. This finding indicates the need for individualized attention to the gait of children with musculoskeletal pain.